PENGARUH MODEL EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DI KELAS V SDN 08 VII KOTO SUNGAI SARIAK PADANG PARIAMAN - Feby Valentina; Winda Febrianti Sari (Ensiklopedia Education Review, 2022)
This research is motivated by the low learning outcomes of science, especially the fifth grade students of SDN 08 VI Koto Sungai Sariak Padang Pariaman. One of the factors causing low student learning outcomes is teacher center learning, so that students are less interested in learning and students are not directly involved in learning. The purpose of this research is to prove whether there is an effect of example non example on learning outcomes of science in class V SDN 08 VII Koto Sungai Sariak Padang Pariaman. This research is an experimental study with a posttest-only control design. The sampling technique in this study was Total Sampling, all fifth grade students were sampled in this study. The primary data in this study is the value of the posttest results. Meanwhile, secondary data was obtained from the value of the IPA test results for class V. The data analysis technique used in this study was the requirements analysis test and hypothesis testing with the t-test. The average posttest score obtained in both classes is. the experimental class is 78.90 and the control class is 77.09 with a difference of 1.81. The criteria for testing the titu price compared to the table are accepted Ho if tcount < table and reject H. if tcount has another value. The table price with a 0.05 and dk 41 is 1.68. From the research, it was found that tcount 2.51, because tcount < ttable and this is not in the acceptance of Ho, so Ha, accepted means that there is a difference in learning outcomes between learning using the Influence model of non-example and conventional learning. It can be concluded that there is an effect of using the example non example model on the learning outcomes of science class V SDN 08 VII Koto Sungai Sarik Padang Pariaman.